Enhancing Assurance Services Using Non-Renewable Resources Standard (NR0401) “Constructive Materials: Applied Research for Kufa Cement Factory (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The importance of this study stems from the importance of preserving the environment and creating a clean sustainable environment from waste and emissions and all the operations of industrial companies in general and cement companies in particular by activating sustainability accounting standards. The research aims to identify and diagnose deviations in violation of sustainability standards by employing the non-renewable resources standard (NR0401) For the construction industries to create a sustainable audit environment, the deductive approach was followed in the theoretical side and the inductive and descriptive approach to the practical side. The most important results of the research were the possibility of applying sustainability accounting standards in general and the NRO401 standard for construction materials in particular for their ability to identify and diagnose deviations in the work of industrial facilities such as the Kufa factory for the industry Cement and to determine the volume and percentages of polluting emissions that violate sustainability standards and thus develop the quality of the audit work and improve the assurance services for the report of the Office of the External Auditor for Global Warming Lists in accordance with Standard 3410,As for the most important recommendations of the research, it was the necessity of the external auditor’s office to use the international auditing standards (Assurance Standard 3400) to improve their assurance services.Keywords: Assurance services, Standard 3410, Warming Lists in accordance, Standard (NR0401).